2007
DOI: 10.1002/jmv.20920
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the VP7 gene of human rotavirus G1 isolated in Japan, China, Thailand, and Vietnam in the context of changing distribution of rotavirus G‐types

Abstract: Over the last decade, rotavirus G1 has represented the most common genotype worldwide. Since 2000, the prevalence of rotavirus G1 has decreased in some countries such as Japan and China. To monitor the trend of the VP7 encoding gene of rotavirus G1, we performed a sequence analysis of 74 G1 rotavirus strains isolated in Japan, China, Thailand, and Vietnam during the period from 2002 to 2005. The phylogenetic tree showed that all of the studied G1 strains from the four countries clustered into lineage III, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
2
20
0
3
Order By: Relevance
“…Other studies (including our study) described the Wa strain as representative of lineage III [Jin et al, 1996;Berois et al, 2003;Parra et al, 2005Parra et al, , 2007aArista et al, 2006]. This finding suggests that VP7 lineage III of all 74 G1 strains isolated in Japan, China, Vietnam, and Thailand [Trinh et al, 2007] and VP7 lineage I of Korean G1 strains in this report belong to the same lineage and further standardize VP7 lineage I as described by Jin et al (1996). Therefore, it is concluded that recent G1 strains belonging to VP7 lineage I were circulating in Korea as well as Asian countries, such as Japan, China, Vietnam, and Thailand.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Other studies (including our study) described the Wa strain as representative of lineage III [Jin et al, 1996;Berois et al, 2003;Parra et al, 2005Parra et al, , 2007aArista et al, 2006]. This finding suggests that VP7 lineage III of all 74 G1 strains isolated in Japan, China, Vietnam, and Thailand [Trinh et al, 2007] and VP7 lineage I of Korean G1 strains in this report belong to the same lineage and further standardize VP7 lineage I as described by Jin et al (1996). Therefore, it is concluded that recent G1 strains belonging to VP7 lineage I were circulating in Korea as well as Asian countries, such as Japan, China, Vietnam, and Thailand.…”
Section: Discussionmentioning
confidence: 47%
“…Considerable genetic diversity has been reported on VP7 gene analysis of G1 strains and at least four major global lineages have arisen among the viruses collected from diverse geographic locations [Jin et al, 1996;Maunula and von Bonsdorff, 1998;Berois et al, 2003;Parra et al, 2005;Arista et al, 2006;Araujo et al, 2007;Trinh et al, 2007]. In the current study, the phylogenetic analysis revealed differences in the VP7 genetic lineages among Korean G1 strains.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A total of 131 sequences of the G1 rotaviruses, including our 36 sequence data from China, Japan, and Vietnam (15,22,26), which did not include any gaps in the alignment for the entire coding region of VP7 genes, were collected from GenBank. Sequence alignment was performed using CLUSTAL X (21).…”
mentioning
confidence: 99%